Baby tsina - Leary, William C.
"Alyas Baby Tsina/Alias Baby China (1984) was based on a true legal story of Evelyn Duave Ortega, aka Baby Tsina (She was called this alias in court documents because she looked Chinese. Otherwise there are no references to anything Chinese in her story or the film). Duave was found guilty in 1971 of murder, and several appeals while on death row culminated in a Supreme Court decision seven years later that declared her innocent and released her from prison."--https://www.imdb.com/title/tt0185859/plotsummary?ref_=tt_ov_pl"